A Note on Reference to Kinds in Mandarin: the N-leikind Compound - Li XuPing (Studies in Chinese Linguistics, 2017)
This squib examines a special kind-referring expression in Mandarin Chinese, the N-leikind compound. We show that like Mandarin bare nouns, N-leikind compounds also denote kinds, but they can only be instantiated by sets of (sub) kind entities at type <k, t>, and not sets of individuals at type <e, t>. Specifically, those kind entities belong to basic-level categories in some folk taxonomy. We claim that N-lei is the nominalization counterpart of the classifier phrase lei-N, and it denotes superkinds, which are instantiated by sets of subkind entities. Accordingly, Mandarin bare nouns are comparable to bare plurals in English, whereas N-lei is comparable to definite singulars in English.